Efektivitas Kepemimpinan Manajerial Kepala Sekolah dalam Pengelolaan Sekolah Dasar - Widyanti, Kukuh; Taufiq Harris; A. Faizin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the strategic role of the school principal as an educational manager responsible for creating a quality learning environment to achieve an effective school. The purpose of this study is to identify and analyze the managerial role of school principals as well as the supporting and inhibiting factors in realizing effective schools at UPT Satuan Pendidikan SDN Orobulu and SDN Krengih, Rembang District, Pasuruan Regency. This study uses a qualitative method with a case study approach. Data collection was carried out through in-depth interviews, direct observation, and analysis of official school documents. Preliminary findings indicate that the managerial competence of principals in strategic planning, resource organization, and supervision has a direct impact on improving the quality of learning and school organizational effectiveness. Key supporting factors include innovative programs and community involvement, while inhibiting factors are related to limited facilities and organizational structure. The results of this study are expected to provide recommendations for the development of educational management at the elementary school level.